A new species of crinoid-associated Periclimenes from Honduras (Crustacea: Decapoda: Palaemonidae) - de Grave, Sammy (Zootaxa, 2014)
A new species of crinoid associated Periclimenes, P. rincewindi sp. nov. is described from the Bay Islands (Honduras) in the Caribbean. The species associates with the swimming crinoid, Analcidometra armata and displays a unique colour pattern. Morphologically, the new species is closely related to the other known crinoid associates in the Caribbean, specifically Periclimenes crinoidalis, from which it can be distinguished by a suite of relatively minor morphological features.